Fostering Undergraduate Students' Digital Skills in EFL Class - Aulia, Vivi (TELL - US JOURNAL, 2019)
AbstractThis research aims at knowing what kinds of efforts have been carried out by EFL teachers to foster undergraduate students in some universities in Banjarmasin. Besides that, this research also wants to know the advantages, the obstacles, and the challenges faced by EFL teachers in Banjarmasin fostering undergraduate students’ digital skills. This research takes place toward 15 EFL teachers in some universities in Banjarmasin who are selected as the participants to deliver information through questionnaire and interview section. The questionnaire item consists of six elements of digital skills and its practice that are expected to be employed by EFL teachers in their classes while interview guide gains the additional information further on clarifying the advantages, the obstacles, and the challenges they face on fostering students’ digital skills. The result of questionnaire shows that during a semester, the frequency of exploring digital-based learning is 65% from the whole meeting course duration at the average for all the EFL teachers under this research. Furthermore, the result of interview section shows that fostering students’ digital skills are not always successful in particular situation due to significant factors. Since the implementation of digital learning activities relies much on the availability of internet connection, the quality of internet network, the cost, and the degree of students’ familiarity with the range of digital tools become the essential things to consider. This research concludes that fostering student’ digital skills in EFL class needs optimal preparation, sufficient facilities available, and teaching plan from the teacher to get maximal learning outcomes.